Effects of pongamia methyl esters and its blends on a diesel engine performance, combustion, and emission characteristics. Issue 1 (5th October 2016) - Sivakumar, M.; Shanmugasundaram, N.; Rameshkumar, R.; Syed Thasthagir, M.
Abstract : The investigation of biodiesel and its blends were carried out in order to control the problem of depletion of fossil fuels and environmental degradation. From this study, we are also able to find out the effect of biodiesel derived from non edible oil of pongamia oil and its blends on performance, combustion and emission characteristics of a single cylinder compression ignition diesel engine. Experimental tests were conducted at various load conditions for evaluating the behavior of various proportions of biodiesel blends and with diesel. The engine parameters such as brake thermal efficiency, brake specific fuel consumption (BSFC), brake specific energy consumption (BSEC), exhaust gas temperature and the products of emitted smoke like carbon monoxide (CO), unburnt hydrocarbon (HC), oxides of nitrogen (NOx ), smoke opacity were measured and evaluated. The brake thermal efficiency of blends B20 and B30 with diesel were marginally increased than diesel and brake specific fuel consumption was higher than that of diesel. The HC and CO emissions were reduced while running an engine with blends B20 and B30. Smoke opacity was found to be lower with biodiesel and its blends when compared to diesel. The emission of NOx from all biodiesel and its blends were higher than diesel. The combustion characteristics of biodiesel and its blends were almost identical to that of diesel. From this investigation, it can be concluded that biodiesel derived from pongamia oil and its blends were up to 30% by volume (B30) could be used in conventional diesel engine without any modification. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 269–276, 2017